Determinants for rainwater harvesting adoption: a case study of smallholder farmers in Murang’a County, Kenya - Itemo Irungu, Francis; Yegon, Rebecca; Milkah Muniale, Faith (UoEm, 2024)
Rainwater harvesting has been practiced among smallholder farmers for centuries in many parts of the world. Recently, it has gained more attention due to the reported increasing water demand and the need for sustainable water management. Drawing on data from a cross sectional survey of 384 household heads (HH), the research study explored the determinants for rainwater harvesting among smallholder farmers in Murang’a County, Kenya. Multistage random sampling technique was employed during the survey using KOBO collect software for data collection. The fndings revealed that socio-economic, socio-demographic and institutional factors signifcantly infuenced the adoption of rooftop RWH, mulching, terraces, infltration pits, retention ditches, water bunds, water pans, dams, furrows, negarims and deep ploughing among HH in Murang’a County. The multivariate probit model results showed that household head’s access to credit facilities, land ownership, age, level of income, education level, gender, family size, source of income, membership to farmers’ groups and access to training services positively infuenced rainwater harvesting (RWH) adoption. Similarly, HH membership to farmers group(s) had merits including: social ties, source of information and source of credit which were also key determinants to RWH adoption in the area. The fndings of the present study recommends the relevant stakeholders to carry out training to HH on RWHTs, creation of awareness among youths on merits for RWH adoption, encourage HH to join farmers’ groups and encourage partnership with credit facilities in RWHTs adoption among HH in the region. Results of the present study provide valuable insights into the determinants for rainwater harvesting among smallholder farmers in Murang’a County which can be used to inform policy and practice for widespread adoption.
Keywords: Agricultural water harvesting; Multivariate probit model; Rainwater harvesting technologies; Smallholder farming; Socio-demographic determinants; Socio-economic determinants